Effects of Premating Calcium and Phosphorus Supplementation on Reproduction Efficiency of Grazing Yak Heifers - Zhou, Jia (Animals (Basel), 2021)
SIMPLE SUMMARY: This study was realized to explore the effects of calcium chloride (CaCl) and monocalcium phosphate (MCP) supplementation on the reproductive efficiency of grazing yak heifers. The body weight, serum markers of bone metabolism, and conception and calving rate of grazing yaks in control group and supplementary feeding groups were compared. The results revealed that supplementation with MCP but not CaCl could significantly improve the reproductive performance, possibly due to the improvement in body weight and bone phosphorus storage providing better estrous physiological conditions for grazing yak heifers. The findings of this study may be helpful and instructional to improve the reproductive efficiency of yaks on the Qinghai Tibet Plateau. ABSTRACT: Reproductive efficiency is the main factor limiting yak production on the Tibet Plateau. The purpose of this study was to investigate the effect of supplementation with calcium chloride (CaCl) and monocalcium phosphate (MCP) for 30 days before breeding on body weight (BW) change, serum bone metabolism biomarkers, conception rate, and calving rate of grazing yaks. Ninety 3 year old yak heifers (153.05 ± 6.56 kg BW) were assigned to three treatments (n = 30 per treatment): grazing without supplementation (CONT), grazing plus calcium chloride supplementation (CaCl), and grazing plus monocalcium phosphate supplementation (MCP). Compared with the CONT group, supplementation with CaCl increased the serum concentrations of osteocalcin and decreased the alkaline phosphatase (ALP) levels (p < 0.05); supplementation with MCP increased the average daily gain (ADG), serum concentrations of phosphorus (P) and osteocalcin, conception rate, and calving rate (p < 0.05), whereas it decreased the serum concentrations of hydroxyproline, ALP, and calcitonin (p < 0.05). Both CaCl and MCP supplementation had no effect on serum calcium (Ca) concentration. The ADG, conception rate, and calving rate were higher in the MCP group than in the CaCl group (p < 0.05), while the serum concentrations of hydroxyproline and calcitonin were lower (p < 0.05). It could be concluded that premating supplementation with MCP increased the body weight gain and subsequent conception and calving rate of grazing yaks. Supplementation with MCP had a positive effect on body condition and bone metabolism, thus providing a better estrous condition for grazing yak heifers, which could contribute to enhancing reproduction efficiency.